Karakteristik fish cake dari surimi lele dumbo (Clarias gariepinus) dengan bahan pengikat yang berbeda: Characteristic of fishcake made from african catfish surimi with a different binding agent - Resi Aji, Falentina Margareta; Sahubawa, Latif (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
African catfish is a type of freshwater fish that grows quickly and has a large market share, but low economic value. The economic value of dumbo catfish can be increased by processing surimi as a raw material for fish cake. Cornstarch and potato starch can be used as binding ingredients in fish cake production. The aim of this study was to determine the best mixture of cornstarch and potato flour for processing fishcake from African catfish surimi based on hedonic, microbial, and calorific values. Surimi for African catfish was produced by the addition of 0.4% sodium alginate flour and 0.5% CaCl2. The treatments in this study were the ratio of cornstarch and potato flour to the amount of surimi used: P0 (10%:0%), P1 (7.5%:2.5%), P2 (5%:5%), P3 (2.5%:7.5%), and P4 (0%:10%). The parameters analyzed included surimi gel strength, chemical composition, hedonics, calorie calculations, and microbial contamination of the fish cakes during storage. The results of the characterization of surimi have gel strength (1,042.8 g/cm2); moisture content (55.48%); fat (4.74%); ash (0.6%); and protein (15.05%). Different formulations of corn starch and potato starch had a significant effect on the nutritional composition of fishcakes, with average moisture content (43.84±0.2%), fat (10.32±0.57%), ash (1.83±0.41%), and protein (11.31±0.12%). The calorific value of the fishcake products was 45 kcal from 5 g fat, 25 kcal from 6 g protein, and 80 kcal from 20 g carbohydrates. The TPC and TVB-N fishcake test results were 1.0x105 cfu/g and 10.94 mg/100 g. Treatment P1 produced fishcakes that were most liked by the panelists, with a total calorific value of 150 kcal per serving size (2 pcs), as well as TPC and TVB-N values that were still within safe limits until the 10th day of storage at a temperature of -18℃.